Subjetividad y lazo social hoy. Conflicto, adicciones, atención psicosocial - Arango Arias, Ana Lucía (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2022)
This book gathers works derived from research carried out by some of the members of the Red de Investigaciones en Subjetividad y Lazo Social (Subjectivity and Social Bond Research Network). It consists of six academic writings, five of Colombian origin and one of Mexican origin, which converge in their interest to give rise to conversation and encourage reflection on the categories of subjectivity and social bond, and how they can be thought from the psychoanalytic discipline. In fact, the book itself is one of the ways forged to articulate the work of the network, to sustain the meetings, to advance in the discussions and to maintain the thread of the discussion, weaving increasingly fruitful links among us, which we hope can also be externalized so that the questions about the complexity of subjectivity and the social bond continue to circulate not only among the members of the network, but also in the different places where it can be received.